Ventral Rectopexy for Rectal Prolapse and Obstructed Defecation - Cullen, John; Rosselli, Jorge M.; Gurland, Brooke H. (Clinics in Colon and Rectal Surgery, 2012)
Ventral rectopexy has gained popularity in Europe to treat full-thickness rectal external and internal prolapse. This procedure has been shown to achieve acceptable anatomic results with low recurrence rates, few complications, and improvements of both constipation and fecal incontinence. The authors review the principles, techniques, and outcomes of ventral rectopexy.
Keywords: anterior ventral rectopexy; rectal prolapse